2008
DOI: 10.1111/j.1463-1326.2007.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐fat diet on glucose homeostasis and gene expression in glucokinase knockout mice

Abstract: gk(del/wt)mice showed early-onset persistent hyperglycaemia, raised glycated haemoglobin levels, impaired GSIS and glucose tolerance but no change in plasma cholesterol, non-esterified fatty acids or triglyceride levels. After HFD feeding, insulin levels of gk(del/wt)mice were less than half that of gk(wt/wt)mice, although they were equivalent to gk(wt/wt)mice on CD. While gk(wt/wt)mice maintained moderate hyperglycaemia, gk(del/wt)mice became overtly diabetic, with worsened glucose tolerance. A GKA (GKA50) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 41 publications
3
41
0
1
Order By: Relevance
“…Table 1 summarises the data for those genes in which changes were observed, either greater than twofold or statistically significant (for full gene list, see Gorman et al (2008)). A marked increase in insulin gene expression was observed, consistent with the individual gene Taqman.…”
Section: Gka71 Is a Potent Activator Of Human Pancreatic Gk And Acutementioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 summarises the data for those genes in which changes were observed, either greater than twofold or statistically significant (for full gene list, see Gorman et al (2008)). A marked increase in insulin gene expression was observed, consistent with the individual gene Taqman.…”
Section: Gka71 Is a Potent Activator Of Human Pancreatic Gk And Acutementioning
confidence: 99%
“…Male C57Bl/6J mice were 8-10 weeks of age (22-24 g) and male Hannover Wistar rats 8-9 weeks of age (230-260 g). Male global heterozygous GK knockout (gk del/wt ) and wild-type (gk wt/wt ) mice were used between 10 and 16 weeks of age; these animals were generated as described previously (Gorman et al 2008). All procedures were carried out in accordance with the Animals (Scientific Procedures) Act 1986.…”
Section: Experimental Animals and Islet Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the report by Grimsby et al in 2003 [5], several glucokinase activators (GKAs) have been developed, and these have been shown to lower blood glucose in several animal models of type 2 diabetes [5][6][7][8][9][10][11][12]. In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%